The sum of the first six terms of a geometric series can be calculated using the formula:
S = a * (1 - r^n) / (1 - r)
where:
S = sum of the first n terms
a = first term (2)
r = common ratio (3)
Plugging in the values:
S = 2 * (1 - 3^6) / (1 - 3)
S = 2 * (1 - 729) / -2
S = 2 * (-728) / -2
S = -1456 / -2
S = 728
Therefore, the sum of the first six terms of the geometric series is 728.
calculate the sum of the first six terms of a geometric series with first term 2 and common ratio 3.(1 point) responses 364 364 242 242 728 728 186 186 skip to navigation
1 answer